2019
DOI: 10.3389/fimmu.2019.03009
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in Pain: Harnessing Endogenous Anti-Inflammatory Signaling for Improved Pain Management

Abstract: Current pain therapeutics offer inadequate relief to patients with chronic pain. A growing literature supports that pro-inflammatory cytokine signaling between immune, glial, and neural cells is integral to the development of pathological pain. Modulation of these communications may hold the key to improved pain management. In this review we first offer an overview of the relationships between pro-inflammatory cytokine and chemokine signaling and pathological pain, with a focus on the actions of cytokines and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(95 citation statements)
references
References 214 publications
(237 reference statements)
2
91
1
1
Order By: Relevance
“…We also observed younger age was associated with MSMP, which could be due to higher physical workload and mental stress before retirement in the MSMP group, 24 , 66 supporting what Neupane et al 44 suggested that MSMP in midlife often persisted to old age in a MSMP trajectory study over 28 years. Cytokines are believed to play a role in pain modulation 19 , 42 , 64 ; however, we did not observe any association between MSMP and plasma levels of MIF, IL-6, IL-1ÎČ, or TNF-α. Although further studies are needed to confirm this, our findings were consistent with others.…”
Section: Discussioncontrasting
confidence: 90%
“…We also observed younger age was associated with MSMP, which could be due to higher physical workload and mental stress before retirement in the MSMP group, 24 , 66 supporting what Neupane et al 44 suggested that MSMP in midlife often persisted to old age in a MSMP trajectory study over 28 years. Cytokines are believed to play a role in pain modulation 19 , 42 , 64 ; however, we did not observe any association between MSMP and plasma levels of MIF, IL-6, IL-1ÎČ, or TNF-α. Although further studies are needed to confirm this, our findings were consistent with others.…”
Section: Discussioncontrasting
confidence: 90%
“…There is increasing evidence that revealed the role of macrophages including activated M1 macrophages, and inducible nitric oxide synthase (iNOS) in pain conditions in fibromyalgia [21]. Significantly, macrophages can mediate microglial activation through the production of pro-inflammatory cytokines such as IL-1ÎČ, IL-6, and TNF-α [22]. In addition, levels of pro-inflammatory cytokines and chemokines are enhanced in serum and could contribute to inflammation at the systemic level.…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…Recombinant human cytokines and cytokine receptors have been used as therapeutic targets to modulate inflammatory activity, driven in part by the pain patients experience as a result of acute and chronic inflammatory diseases [ 182 , 183 ]. Three core pro-inflammatory cytokines have been of particular interest in this realm: TNF-α, IL-1ÎČ, and IL-6.…”
Section: Therapeutic Advancesmentioning
confidence: 99%